1986
DOI: 10.1159/000118261
|View full text |Cite
|
Sign up to set email alerts
|

ACTH and Attention in Humans:A Review

Abstract: In addition to the hormonal action of corticotropin (ACTH) on the adrenal cortex, this peptide and fragments of it may function as chemical signals in CNS synapses. This report reviews studies on behavioral and psychophysiological effects of ACTH-related neuropeptides. Experiments will be emphasized which applied EEG techniques for the measurement of peptide-induced changes on aspects of information processing in man. It is proposed to conceptualize the pattern of actions of ACTH-related neuropeptides as a blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Holland and Gallagher have found that the CEA is involved in increasing attention to significant events, but not in tuning out redundant cues [10]. Thus, the idea that the central amygdala is the site of action of ORG 2766 seems in agreement with an effect of the peptide on non-selective attention, which has been suggested after some lesion studies in rats and after studies on human subjects [3].…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Holland and Gallagher have found that the CEA is involved in increasing attention to significant events, but not in tuning out redundant cues [10]. Thus, the idea that the central amygdala is the site of action of ORG 2766 seems in agreement with an effect of the peptide on non-selective attention, which has been suggested after some lesion studies in rats and after studies on human subjects [3].…”
mentioning
confidence: 79%
“…Fragments and analogs of the adrenocorticotrophic hormone (ACTH) can influence behavior of rats and humans [3,5] and enhance functional recovery after damage to the central and peripheral nervous system [14,18]. Chronic administration of the ACTH(4-9) analog ORG 2766 affects the behavior of brain lesioned and aged rats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological characteristics of the acute effects of ACTH 4–10 on ERP signs of attention in humans have been well documented in foregoing studies [3, 4, 12]. Effects on the ‘processing negativity’ (PN) of the ERP which is a classical marker of focussed attention were found to increase in strength linearly with logarithmically increasing doses of ACTH 4–10 (0.1–10 mg i.v.)…”
Section: Introductionmentioning
confidence: 99%
“…Together with other natural peptides such as α-melanocytestimulating hormone (α-MSH, corresponding to acetylated ACTH 1–13 amide) and synthetic deviations this group is called melanocortins which are known to be most potent regulators of neurobehavioral functions in animals and man [1, 2]. In humans, ACTH and its behaviorally active fragment ACTH 4–10 as well as ORG 2766 (an analog of ACTH 4–9) have been consistently found to weaken event-related brain potential (ERP) signs of selective attention [3, 4]. Substances in those experiments were administered systemically, i.e.…”
Section: Introductionmentioning
confidence: 99%